Influence of amount and frequency of protein supplementation to steers consuming low-quality, cool-season forage: intake, nutrient digestibility, and ruminal fermentation. (13th April 2021) - Cappellozza, Bruno I; Bohnert, David W; Reis, Maria M; Swanson, Kendall C; Falck, Stephanie J; Cooke, Reinaldo F
Abstract: This experiment evaluated the influence of protein supplementation frequency (SF ) and amount offered on intake, nutrient digestibility, and ruminal fermentation by rumen-fistulated beef steers consuming low-quality [2.9% crude protein (CP ); dry matter (DM ) basis], cool-season forage. Seven Angus × Hereford steers (300 ± 27 kg) fitted with ruminal cannulas were randomly assigned to 1 of 7 treatments in an incomplete 7 × 4 Latin square. Treatments, in a 2 × 3 factorial design plus a non-supplemented control (CON ), consisted of 2 levels of supplemental soybean meal, 100% (F ) or 50% (H ) of the estimated rumen-degradable protein requirement, provided daily (D ), once every 5 d (5D ), or once every 10 d (10D ). Experimental periods were 30 d and dry matter intake (DMI ) was measured from days 19 to 28. On days 21 (all supplements provided) and 30 (only daily supplements provided; day immediately prior to supplementation for 5D and 10D treatments) ruminal fluid was collected for ruminal pH, ammonia-N (NH 3 ), volatile fatty acids (VFA ), and determination of ruminal fermentation variables. Forage and total DM, organic matter (OM ), and nitrogen (N ) intake increased with supplementation ( P ≤ 0.04). However, a linear effect of SF × amount of supplement interaction was observed for forage and total DM, OM, and N intake ( P ≤ 0.04), with each variable decreasing as SF decreased, but the decrease being greater with F vs. H. Apparent total tract DM, OM, and neutral detergent fiber digestibility was not affected by supplementation or amount of supplement provided ( P ≥ 0.10). In contrast, N digestibility increased with supplementation and for F vs. H ( P < 0.01). Digestibility of DM, OM, and N increased linearly as SF decreased ( P ≤ 0.03). When all supplements were provided, ruminal NH3, total VFA, and molar proportions of all individual VFA increased with supplementation ( P ≤ 0.04), whereas acetate:propionate ratio decreased ( P < 0.01). When only daily supplements were provided, none of the aforementioned fermentation parameters were affected ( P ≥ 0.09). In summary, reducing the amount of supplemental CP provided to ruminants consuming low-quality forages, when supplementation intervals are >5 d, can be a management tool to maintain acceptable levels of DMI, nutrient digestibility, and ruminal fermentation while reducing supplementation cost.